Promotion of Local Designers at the Jogja Fashion Week 2023 - Hidayah, Al Hibni Fadhil; Widyasari, Wulan (Jogjakarta Communication Conference (JCC), 2025)
Jogja Fashion Week (JFW) is an annual event initiated by the Department of Industry and Trade of the Special Region of Yogyakarta (Disperindag DIY) to promote local designers and strengthen Yogyakarta’s position as a national and global fashion hub. This study aims to analyze the promotional strategies implemented by Disperindag DIY to enhance the exposure of local designers through Jogja Fashion Week 2023. This research employs a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews with relevant officials, observations, and documentation from various sources. Data analysis was conducted using data reduction, data presentation, and conclusion verification methods. The findings reveal that the promotional strategies used a promotional mix consisting of publicity through digital promotions of social media Instagram and websites, advertising on various digital platforms, direct marketing through exhibitions and fashion shows, as well as word-of-mouth promotion supported by influencers. A SWOT analysis highlights that the primary strength of JFW 2023's promotional strategy is its long-established reputation and full support from the DIY government. However, challenges remain in terms of limited promotional budgets and competition with international fashion brands. The study concludes that the implemented promotional strategies have successfully increased local designers' participation and the exposure of their products to a broader market. However, improvements in promotional management and stronger collaborations with stakeholders are still necessary to enhance promotional effectiveness in the future.